Pengaruh Teknik Budidaya Alternatif Menggunakan Zone Cooling Terhadap Pertumbuhan dan Hasil Benih Kentang Di Desa Karangmangu Kecamatan Baturaden - Rennanti Lunnadiyah Aprilia; Nurlaila Fatmawati (Jurnal Kridatama Sains dan Teknologi, 2020)
Potatoes are one of the horticultural commodities that are in demand by the public because of their nutritional content and can meet carbohydrate needs. Currently, the need for potato tubers has not yet fulfilled people's needs optimally. This is because the need for potato seeds is still inadequate both in quality and quantity. This study aims to (1) determine the response of potato seeds using hydroponic and aeroponic cultivation techniques, (2) determine the temperature of the best nutrient solution to be applied to potato seeds. The method used was a completely randomized design (CRD). Using factorial experiments. The factors tested were the cultivation technique and nutrient solution. Alternative cultivation techniques have 2 levels, namely Aeroponics and Hydroponics, while the temperature solution has 4 levels, namely normal average temperature (23oC), 15oC, 19oC and 24oC. In total there were 8 treatments. The results of the study were analyzed using the F test then continued using DMRT with a level of 5%. The results showed that the response to potato growth was good using aeroponic techniques, while the yield components were good using hydroponic techniques. The best solution temperature is 23oC.